Control of Germline torso Expression by the BTB/POZ Domain Protein Pipsqueak Is Required for Embryonic Terminal Patterning in Drosophila. - Grillo, M.; Furriols, M.; Casanova, J.; Luschnig, S. (Genetics, 2011)
Early embryogenesis in Drosophila melanogaster is controlled by maternal gene products, which are deposited in the egg during oogenesis. It is not well understood how maternal gene expression is controlled during germline development. pipsqueak (psq) is a complex locus that encodes several nuclear protein variants containing a PSQ DNA-binding domain and a BTB/POZ domain. Psq proteins are thought to regulate germline gene expression through epigenetic silencing. While psq was originally identified as a posterior-group gene, we show here a novel role of psq in embryonic terminal patterning. We characterized a new psq loss-of-function allele, psq(rum), which specifically affects signaling by the Torso (Tor) receptor tyrosine kinase (RTK). Using genetic epistasis, gene expression analyses, and rescue experiments, we demonstrate that the sole function impaired by the psq(rum) mutation in the terminal system is an essential requirement for controlling transcription of the tor gene in the germline. In contrast, the expression of several other maternal genes, including those encoding Tor pathway components, is not affected by the mutation. Rescue of the psq(rum) terminal phenotype does not require the BTB/POZ domain, suggesting that the PSQ DNA-binding domain can function independently of the BTB/POZ domain. Our finding that tor expression is subject to dedicated transcriptional regulation suggests that different maternal genes may be regulated by multiple distinct mechanisms, rather than by a general program controlling nurse-cell transcription.